Resveratrol Potentiates Growth Inhibitory Effects of Rapamycin in PTEN-deficient Lipoma Cells by Suppressing p70S6 Kinase Activity. (17th February 2016) - Leipert, Jenny; Kässner, Franziska; Schuster, Susanne; Händel, Norman; Körner, Antje; Kiess, Wieland; Garten, Antje
ABSTRACT: Patients with phosphatase and tensin homolog ( PTEN ) hamartoma tumor syndrome and germline mutations in PTEN frequently develop lipomatosis, for which there is no standard treatment. Rapamycin was shown to reduce the growth of lipoma cells with heterozygous PTEN deficiency in vitro, but concomitantly induced an upregulation of AKT phosphorylation. Since it was shown that resveratrol stabilizes PTEN, we asked whether co-incubation with resveratrol could suppress the rapamycin-induced AKT phosphorylation in PTEN -deficient lipoma cells. Resveratrol incubation resulted in decreased lipoma cell viability by inducing G1-phase cell cycle arrest and apoptosis. PTEN expression and AKT phosphorylation were not significantly changed, whereas p70S6 kinase (p70S6K) phosphorylation was reduced in PTEN -deficient lipoma cells after resveratrol incubation. Rapamycin/resveratrol co-incubation significantly decreased viability further at lower doses of resveratrol and resulted in decreased p70S6K phosphorylation compared to rapamycin incubation alone, suggesting that resveratrol potentiated the growth inhibitory effects of rapamycin by reducing p70S6K activation. Both viability and p70S6K phosphorylation of primary PTEN wild-type preadipocytes were less affected compared to PTEN -deficient lipoma cells by equimolar concentrations of resveratrol. These results support the concept of combining chemopreventive natural compounds with mammalian target of rapamycin (mTOR) inhibitors to increase the efficacy of chemotherapeutic drugs for patients suffering from overgrowth syndromes.